2012
DOI: 10.3168/jds.2011-4732
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the acetyl-coenzyme A acyltransferase 2 (ACAA2) gene is associated with milk yield in Chios sheep

Abstract: The objective of this work was to identify single nucleotide polymorphisms (SNP) in the ovine acetyl-coenzyme A acyltransferase 2 (ACAA2) gene and investigate their association with milk production traits. Molecular characterization was accomplished by sequencing the entire coding region and the 3' and 5' untranslated regions (UTR) of the ACAA2 gene from individuals of the Chios sheep bred in Cyprus. All exons appeared to be monomorphic except for the last exon, for which a single SNP located in the 3' UTR of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
4
20
1
Order By: Relevance
“…As a transcriptional activator of HMGCS2 27 , peroxisome proliferator-activated receptor alpha, which is target gene of XLOC_001424 and both upregulated, affects the energy balance between glucose and ketone bodies within the mitochondria 18 . Indeed, energy metabolism disorders are an important aspect of NASH, as indicated by the fact that insulin resistance promotes the production of arachidonic acid (FADS2) 28 and TG (DGAT2) 29 and affects mitochondrial fatty acid beta-oxidation by acetyl-CoA acyltransferase 2 (ACAA2) 30 , which is the target of XLOC_023704 in early NASH minipigs, and the target gene and lncRNA both upregulated. High levels of ketone bodies are caused by CYP2E1 31 which is the target gene of XLOC_017612, and ADH4 overexpression, which leads to the production of ROS 18 .…”
Section: Discussionmentioning
confidence: 99%
“…As a transcriptional activator of HMGCS2 27 , peroxisome proliferator-activated receptor alpha, which is target gene of XLOC_001424 and both upregulated, affects the energy balance between glucose and ketone bodies within the mitochondria 18 . Indeed, energy metabolism disorders are an important aspect of NASH, as indicated by the fact that insulin resistance promotes the production of arachidonic acid (FADS2) 28 and TG (DGAT2) 29 and affects mitochondrial fatty acid beta-oxidation by acetyl-CoA acyltransferase 2 (ACAA2) 30 , which is the target of XLOC_023704 in early NASH minipigs, and the target gene and lncRNA both upregulated. High levels of ketone bodies are caused by CYP2E1 31 which is the target gene of XLOC_017612, and ADH4 overexpression, which leads to the production of ROS 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, informative polymorphisms were only observed for the ACAA2 and FASN genes (Tables 1 and 2). Allelic frequencies in the ACAA2 SNP locus were 0.47 and 0.53 for the C and T alleles, respectively, similarly to Orford et al (2012) and Miltiadou et al (2017a), while genotypic frequencies were found to deviate from Hardy-Weinberg equilibrium (online Supplementary Table S3), consistently with our latest study where the frequency of the genotypes carrying the T allele was higher probably due to directional animal selection for increased milk yield (Miltiadou et al, 2017a). In the FASN SNP locus, the respective frequencies for the C and T alleles were 0.67 and 0.33 (online Supplementary Table S3), whereas the C allele frequency reported for the Altamurana and Gentile di Puglia breeds was 0.93 and 1 in Sarda breed (Crisà et al, 2010), suggesting important inter-breed differences.…”
Section: Resultsmentioning
confidence: 83%
“…In 2007, the flock was sampled by collecting blood samples from all the 386 adult animals from 104 paternal half-sib families (Orford and others 2012). From these samples, 192 individuals were selected randomly for genotyping and included all 32 males and 160 females.…”
Section: Methodsmentioning
confidence: 99%